2015
DOI: 10.1080/10236244.2015.1034956
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stocking density on growth and seven physiological parameters with assessment of their potential as stress response indicators for the Atlantic salmon (Salmo salar)

Abstract: Inappropriately high stocking density can lead to chronic stress that causes many problems in fish culture. We examined the influence of stocking density on growth performance and a number of key serum parameters of Atlantic salmon (Salmo salar) to investigate stress-induced changes. Salmon were reared at low-density (~7.57-15.71 kg/m 3 , initial to final density), mediumdensity (~15.12-31.11 kg/m 3 ), and high-density (~30.18-61.34 kg/m 3 ) stocking levels for 10 weeks. The results showed that stocking densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In this study, the salmon in the HSD group showed significantly higher cortisol level than those in the LSD and MSD groups. These findings are consistent with earlier studies on Atlantic salmon (Mazur & Iwama ; Liu, Liu & Wang ) and those in other fish species such as Asian seabass Lates calcarifer and Senegalese sole Solea senegalensis (Salas‐Leiton et al . ; Sadhu, Sharma, Joseph, Dube & Philipose ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the salmon in the HSD group showed significantly higher cortisol level than those in the LSD and MSD groups. These findings are consistent with earlier studies on Atlantic salmon (Mazur & Iwama ; Liu, Liu & Wang ) and those in other fish species such as Asian seabass Lates calcarifer and Senegalese sole Solea senegalensis (Salas‐Leiton et al . ; Sadhu, Sharma, Joseph, Dube & Philipose ).…”
Section: Discussionsupporting
confidence: 93%
“…(2004) observed similar effects on plasma cortisol and lymphopenia in male jundià ( Polycentrus jundia , Coutinho et Wosiacki, Perciformes, Polycentridae) after acute and chronic stress, respectively, induced by classical aquaculture management procedures (handling and high density of fish in the tank, respectively). In salmon aquaculture, several classical procedures have also been shown to be detrimental to fish health status and welfare (Liu et al., 2015; Turnbull et al., 2005). For instance, handling during a vaccine injection can be a cause of stress, inducing immune suppression and thus being a limiting factor for vaccine efficacy (Sommerset et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Handling and overcrowding have already been demonstrated to be stressful situations resulting in activation of the hypothalamus–pituitary–interrenal axis (i.e. cortisol or other related stress indicators variations; Erikson & Misimi, 2008; Liu et al., 2015; Merkin et al., 2010). However, the consequences of these procedures on salmon‐sea lice interactions have never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that high stocking densities were associated with decreases in SOD activity in some sh [39,40] and shrimps [41,42].…”
Section: Discussionmentioning
confidence: 98%